Evaluation of risk factors, causative pathogens, and treatment in recurrent percutaneous nephrostomy catheter-related urinary tract infections in cancer patients. Issue 14 (7th April 2023) - Mert, Duygu; Iskender, Gulsen; Kolgelier, Servet; Ertek, Mustafa
Abstract : Introduction: In cancer patients, percutaneous nephrostomy (PN) catheters can be used to relieve obstruction from chemotherapy, radiation therapy, or surgery, thereby improving kidney function and preventing further kidney damage. One of the complications of PN catheters is infections. Recurrent infections may delay chemotherapy, increase antimicrobial resistance with frequent antibiotic use, deteriorate the quality of life of patients, and increase costs. In this study, it was aimed to evaluate risk factors, causative pathogens, and treatment in recurrent PN catheter-related urinary tract infections in cancer patients. Material and method: Cancer patients with PN catheter-associated urinary tract infection who were followed-up in the Infectious Diseases and Clinical Microbiology Clinic between January 1, 2012 and December 31, 2021 were included in the study. Results: The total catheterization time, and occurrence of preinfection catheter replacement, active chemotherapy, and kidney stones were significantly higher in patients with recurrent infection when compared to the other group ( P = .000, P = .000, P = .007, and P = .018, respectively). ESBL-positive Escherichia coli and ESBL-positive Klebsiella pneumoniae were most commonly isolated from the PN catheter urine cultures of patients with recurrent infections. Discussion: Long-term use of the PN catheter increases the risk of urinary tract infection and sepsis. In this study, the total catheterization time, and occurrence of preinfection catheter replacement, active chemotherapy, and kidney stones were found to be risk factors for the development of recurrent PN catheter-related urinary tract infection in cancer patients. Conclusion: It is important to know the risk factors in recurrent PN catheter-related urinary tract infections in cancer patients, take maximum protective measures, and follow-up. Knowing both the causative profile and the resistance rates will increase the chance of success in the treatment when empirical treatment is required. It should also be noted that these patients should be included in the group of patients who need prophylaxis for urinary tract infection.